(untitled) (Academia Journal of Medicine, 2019)
Background: Diabetes mellitus is described as a group of metabolic disorders of multiple etiology characterized by chronic hyperglycemia associated with disturbances of carbohydrate, fat and protein metabolism due to absolute or relative deficiency of insulin secretion and/or action. Diabetes mellitus is associated with significant long term sequels, particularly damage or dysfunction of various organs especially kidneys, eyes, nerves, heart and blood vessels. Subjects and Methods: A pre-structured and pre-tested proforma was used to collect the data. Informed consent was taken from all cases and control subjects. Base line data including age and sex, detailed medical history including conventional risk factors, clinical examinations and relevant investigations were included as part of the methodology. Results: The mean serum FBS level among cases was 146.94±54.99 mg % as compared to 86.71±9.71 mg % among controls. There was highly significant difference in serum FBS levels among cases and controls. Conclusion: The mean serum PPBS level among cases was 244.26±96.47 mg % as compared to 111.96±8.85 mg % among controls. There was highly significant difference in serum PPBS levels among cases and controls.